The cost to perform uterine fibroid embolisation in the Australian public hospital system. Issue 1 (2nd December 2019) - Clements, Warren; Moriarty, Heather K; Koukounaras, Jim; Joseph, Tim; Phan, Tuan; Goh, Gerard S
Abstract: Introduction: Uterine fibroids have the potential to cause morbidity, and there is a substantial cost to both the healthcare system and society. There is support for minimally invasive intervention, and uterine fibroid embolisation (UFE) is an established cost‐effective option for women wishing for an alternative to surgery. There is a lack of local Australian costing data to compliment use in the public hospital system, and we offer a costing analysis of running a public hospital service. Methods: We reviewed the costs for 10 sequential uterine fibroid embolisation cases, by assessing the direct and indirect hospital costs. Results: The total cost of providing a uterine fibroid embolisation service using our model in a public hospital including initial outpatient assessment, procedure costs, overnight hospital ward stay and outpatient follow‐up is $3995 per admission. Conclusion: Using our model, the overall cost to perform this procedure is low, and lower than prior estimates for surgical alternatives. We encourage government and regulatory bodies to support UFE through guidelines and remuneration models, and encourage more public Australian interventional radiology departments to offer this service.